Kesiapan Mengajar Mahasiswa Matematika Tingkat AkhirUniversitas Muhammadiyah Surakarta Ditinjau Dari Permasalahan Di SMP - Nurzayani, Rofiqoh (2016)
Rofiqoh Nurzayani/A410110119. Readiness Of Teaching Final Student Mathematics Storey;Level of University Muhammadiyah Surakarta Evaluated The study aims at evaluating: (1) readiness of teaching University Muhammadiyah Surakarta mathematics student, (2) problem of study process, (3) solution from problem of study process. this Research type is qualitative with usedby research method that is sampel survey method. Research population all semertar student 7 majors Education of Mathematics University Muhammadiyah Surakarta. Taken sampel at random counted 20 student which have executed program experience of field.Technique Intake of sampel use purposive sampling technique. Technique data collecting with kuesioner method, documentation and interview. Pursuant to result of research obtained by problems that happened at study process among others making plan study execution, use of study method, source of learning, assessment result of learning, understanding about student, organizational of time, and execution study ofclass. Pursuant to strived solution and problems can be known by storey;level ofis readiness of teaching student Education of Mathematics University Muhammadiyah Surakarta reach 95,833% what is the included in category ofis readiness of very high.